Recruitment of beneficial cucumber rhizosphere microbes mediated by amino acid secretion induced by biocontrol Bacillus subtilis isolate 1JN2 - Wei Yang; Xiao Li; Haixia Yan; Yiwen Sun; Diwen Wu; Ying Du; Yuming Luo (Frontiers in Microbiology, 2024)
IntroductionAt present, the use of beneficial microorganisms to control cucumber Fusarium wilt is a widely used method, and the rhizosphere microecological reset is one of the mechanisms involved. However, how biocontrol strains reshape cucumber rhizosphere microecology remains to be further studied.MethodsThe composition changes of cucumber root exudates induced by biocontrol strain 1JN2, the microbial ecology of cucumber rhizosphere and the colonization ability of biocontrol strain 1JN2 in cucumber rhizosphere were analyzed through UHPLC-MS/MS analysis, Illumina high-throughput sequencing and SEM, respectively.ResultsFirst, cucumber plants treated with biocontrol Bacillus 1JN2 reduced the disease severity of Fusarium wilt by 60%. Significant changes in cucumber root exudates were found after 1JN2 inoculation and the contents of four amino acids including glutamine, tryptophan, glycine and glutamic acid were significantly increased. Second, It was found that the bacterial diversity in the rhizosphere of cucumber was significantly increased in both the strain treatment group and the amino acid mixture treatment group, The number of Bacillus was the largest in all dominant populations, exceeded 20% in all treatment groups. The bacteria of Hydrogenispora and Vicinamibacteria were significantly increased after treatment.DiscussionOverall, the results demonstrated that amino acid substances in cucumber root exudates induced by biocontrol strain 1JN2 can shift the cucumber root microenvironment and prevent the occurrence of Fusarium wilt disease.